Lesiones en el fútbol: ¿Quién debe hacerse responsable? - Mundaray, Elena (2026)
Injuries are not an unknown topic in sports practice, much less in soccer. For this reason, the present research work aims to analyze the responsibility behind these events within the professional activity and, if necessary, to make the payment of the due economic compensations for the injury or disability produced. For this purpose, different national labor legislations, regulations applied to soccer, decisions of the FIFA Dispute Resolution Chamber and CAS were studied in order to formulate recommendations to face the conflict generated as a result of an injury.